Analisis Kelayakan Usaha Pendirian Badan Usaha Milik Daerah (BUMD) Perseroda Muratara Energi dan Muratara Agro di Kabupaten Musi Rawas Utara. - Yayuk Marliza; Miki Indika; Anggia Syafitri; Kusnadi Yudha Wiguna; Subianto Subianto; Ryan Octavianie; Herawati Herawati (UNIVED Press, 2023)
The purpose of study was to conduct a business feasibility analysis for Perseroda Muratara Energi and Muratara Argo, north Musi Rawas Regency, South Sumatra Province. Types and sources od data related to this analysis are primary data and secondary data. Secondary data ttaken comes from thhe Regional Goverment and relevant and accountable agencies or stakeholders from laws and regulations, literature books, journals, financial data and other relevant sources. In additions to secondary data, primary data is used to verify and validate data from interviews and focus group disscussion activities so that the data obtained is more compelete and acurate. The data that has been collected isannalyzed using descriptive qualitative methods and with quantitative and qualitative approaches so that the data can be analyzed hlistically. Based on the results of an analysis of business feasibility and regional potential for the establisthment of a Regional Owned Enterprise in Musi regency, North Musi Rawas Regency in 2020, it can be concluded that from a business feasibility perspective: 1) Economic Feasibility Aspects, 2) Market and Marketing feasibility Aspects, 3) Feasibility Aspects Financial, 4) Social and Environmental Cultural Feasibility Aspects, 5) Other aspects consisting can be declaredd very feasible for the establishment of Regional owned Enterprises Perseroda Muratara energi and Muratara Agro North Musi Rawas Regency. In terms of regional potential of North musi Rawas Regency it can be concluded that: (1) Agriculture sector, forestry and fishery, and sector (2) mining and quarrying have the potential to be improved and develoved in the establishment of Regional Owned Enterprises Perseroda Muratara Energi and Muratara aggro Musi Regency north Swamp.